Caracterização molecular de espécies de Potamotrygon (Potamotrygonidae, Myliobatiformes) da planície de inundação do alto rio Paraná, Brasil : variabilidade e diferenciação genética, hibridação e filogeografia. - Maniglia, Thiago Cintra (2010)
The freshwater stingrays from the Potamotrygonidae family are cartilaginous fish of marine origins that invaded the Amazon basin during the Miocene. There are other freshwater species, such as from the Dasyatidae family, but only the stingrays of the Potamotrygonidae are fully adapted and have all their life cycle in freshwater. There are three genus in Potamotrygonidae. Paratrygon and Plesiotrygon with only one species each, and Potamotrygon with 18 species and others to be described. The Amazon basin has the highest diversity of species, with 13 described species, while the Paraná- Paraguay basin has seven species. Most species are endemic, with few species inhabiting more than one basin, for example, P. motoro. In the Upper Paraná River, there are now two species, P. motoro and P. falkneri, which invaded this environment after the construction of Itaipu. In this study we evaluated the genetic variability and genetic differentiation of the potamotrygonids in the Upper Paraná River, the possibility of interspecific hybridization and comparison between populations of P. motoro from the Upper Paraná River, Orinoco River and the Amazon basin. Both species, P. motoro and P. falkneri showed low genetic diversity, however, with some molecular markers, two groups were identified in P. falkneri. More studies are required to confirm this result. The genetic differentiation between the two species was also very low, emphasizing the recent speciation of these two species. Hybrid individuals were detected between P. motoro and P. falkneri in the Upper Paraná River. The analysis between the populations of P. motoro from the Upper Paraná River, Orinoco River and the Amazon basin showed that these populations do not belong to the same species. Therefore, P. motoro should be considered a species complex, and their identification restricted to the Paraná-Paraguay basin, where were described.